Value of the Jirgl flocculation test in the diagnosis of jaundice - Rose, D. P. (1965)
The Jirgl flocculation test has been compared with the combination of the thymol reactions and serum alkaline phosphatase determination recommended by Maclagan in the investigation of 68 patients with jaundice. The test was found to be of value in distinguishing biliary obstruction from other causes of jaundice, but failed to distinguish between extrahepatic and intrahepatic biliary obstruction. Serum glutamic oxalacetic transaminase and serum glutamic pyruvic transaminase estimations were performed in a number of cases, but were found to be of no value in the diagnosis of jaundice.